CLINICAL MANIFESTATIONS OF TUMORS BRAIN (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
he incidence rate of primary brain tumors (PBT) and other CNS tumors in the United Statesfrom 2011 to 2015 was 23.03 cases per 100,000, so the total number of tumor cases was 392,982(CBTRUS (Centra Brain Tumor Registry of the United State). All over the world with newlydiagnosed malignant brain tumors. in 2012, 139,608 men and 116,605 were diagnosed women,amounting to a total of 256,213 person (CTBRUS).